2009
DOI: 10.1021/jp903078x
|View full text |Cite
|
Sign up to set email alerts
|

Quasi-Static Self-Quenching of Trp-X and X-Trp Dipeptides in Water: Ultrafast Fluorescence Decay

Abstract: Time-resolved fluorescence decay profiles of N-acetyl-L-tryptophan-amide (NATA) and tryptophan (Trp) dipeptides of the form Trp-X and X-Trp, where X is another aminoacyl residue, have been investigated using an ultraviolet upconversion spectrophoto fluorometer with time resolution better than 350 fs, together with a time correlated single photon counting apparatus on the 100ps to 20ns time scale. We analyzed the set of fluorescence decay profiles at multiple wavelengths using the global analysis technique. Nan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(33 citation statements)
references
References 46 publications
1
32
0
Order By: Relevance
“…Every protein except A1m-H displayed a short-lifetime component of a few hundred ps, present at all wavelengths. These types of quenching processes have been attributed to Trp interactions with nearby charged residues (37)(38)(39), and the absence of such a feature in A1m-H again indicates that this protein has a local structure different from those of the other eight proteins. The perturbation of local structure and, thus, local solvent exposure can result in different hydration dynamics, making it unreliable to compare the dynamics of A1m-H to those of the other A1m proteins.…”
Section: Resultsmentioning
confidence: 98%
“…Every protein except A1m-H displayed a short-lifetime component of a few hundred ps, present at all wavelengths. These types of quenching processes have been attributed to Trp interactions with nearby charged residues (37)(38)(39), and the absence of such a feature in A1m-H again indicates that this protein has a local structure different from those of the other eight proteins. The perturbation of local structure and, thus, local solvent exposure can result in different hydration dynamics, making it unreliable to compare the dynamics of A1m-H to those of the other A1m proteins.…”
Section: Resultsmentioning
confidence: 98%
“…The existence of dark excited state species [16], or extremely short excited species [17] are well documented. We do not know any literature example in a protein where the lifetime does not significantly change while the intensity changes so much (>200 %).…”
Section: Introductionmentioning
confidence: 99%
“…Work on tryptophanyl dipeptides has been used very elegantly by Knutson and coworkers to investigate the multiexponential decay of tryptophan in light of the rotamer model [22][23]. In these time resolved studies, the authors studied the multiexponential fluorescence decay in the picosecond regime and concluded that it is associated to ground state heterogeneity that may arise from different conformational rotamers of the peptide side chains.…”
Section: Introductionmentioning
confidence: 99%